Histological and Histochemical Features of the Newly Lactating Udderinlocal Breed She Goat (Caprice Hirccus) - Yousif R.Jumaah; Abdul KarimJafar Karim (Institute of Medico-legal Publications Pvt Ltd, 2022)
Six samples of one day post parturition mammary glands of local breed goats were used for this work. The samplesof glands were dissected the tissue specimens were fixed in 10% formalin solution. The specimens were processedaccording to paraffin embedding technique, sectioned at 5-6μm and stained by hematoxylin and eosin, Masson’sTrichrom stains and Verhoff stain. The newly lactating mammary gland was covered by very thick, well glandularskin that measured 210.32±9.03μm. The mammary parenchyma was composed of groups of huge mammarylobes which separated by well vascular thick layer of inter lobar fibrous tissue that measured 986.19±23.10 μm(Thickness). The mean of surface area of mammary lobe was134785.48±15.89μm², it was consisted of numeroussmall size lobules that measured 9848.79±23.75μm² and separated from each other by thin layer of fibro muscularinter lobular connective tissue that measured 138.16±4.11 μm. The lobule was composed of mammary alveoliwhich revealed marked secretory activities. The mean surface area of alveolus was 784.79±19.09 μm² that linedby cuboidal cells that measured 14.11±1.09 μm. Duct system of newly lactating mammary gland was intra lobularduct, large inter lobar duct, largest lactiferous sinus, the lactiferous sinus was drainage to glandular cisterna thatopened into teat cisterna and the later opened into teat canal. Gland cisterna was huge chamber had wide irregularshaped lumen. The mucosa of gland cisterna had few mucosal folds which lined by simple cuboidal epitheliumand supported a lamina propria of dense fibro muscular connective tissue. The epithelium of cisterna which closeto the mammary lobules was supported thick layer of well vascular fibrous connective tissue. Teat cisterna wascomposed of mucosal folds that supported by fibro muscular layer with venous plexus.